GLUCOSE HOMEOSTATIC AND PANCREAS PROTECTIVE POTENTIAL OF TECOMELLA UNDULATA ROOT EXTRACT IN STREPTOZOTOCIN INDUCED DIABETIC RATS . - Lal, Kanwar; Purohit, Ashok; Ram, Heera (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The study was aimed to evaluate glucose homeostatic and pancreas protective potential of Tecomella undulata root extract in streptozotocin induced diabetic rats. Methods: The ethanolic root extract was prepared by following standard soxhlation methods. The experimental design was divided in to control and treated groups for 28 days of comparative experimental schedule. The body and organ weights, serum biochemistry, histo-pathology, hematology and toxicity profiles were assayed by following standard methods and protocols. Results: The treatment of ethanolic extract of root of T. undulata was significantly (p â‰¤ 0.001) reduced glucose levels at 7day, 14day, 21day and 28 days in comparison to standard drug of metformin. Correspondingly, lipid profile i.e. total cholesterol, HDL, VLDL, LDL and triglyceride were also altered significantly. Whereas, body and organs weight and hematological parameters were not shown significant changes. Subsequently, toxicity profile i.e. hepatic and renal parameters were remained under normal ranges. Corresponding, the treatment of ethanolic root extract caused normalcy of histoarchitecture of pancreas in comparison to standard drugs. Conclusion: The results of study illustrated that Tecomella undulata root extract possessing particular kind of phytocompounds which caused glucose homeostatic and pancreas protective potential in diabetic rats.